(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The current study aimed to reveal the relationship between psychological resilience and linguistic intelligence among female students in the Kindergarten Department at the Faculty of Education at Tishrin University. The study sample consisted of (200) female students in the Kindergarten Department. The researcher used the psychological resilience scale consisting of (40) paragraphs prepared by (Salem bin Saleh Al-Azri, 2016), and the linguistic intelligence questionnaire that she developed based on theoretical references and previous studies on linguistic intelligence. The results of the study showed a positive direct relationship between psychological resilience and linguistic intelligence. It also showed differences between the sample members of the "first and fourth year" female students on the psychological resilience scale in favor of the fourth year. It showed that there were differences between the sample members on the linguistic intelligence scale according to the variable of the academic year (first and fourth), in favor of the fourth year